Kerry Houston and Harry White (eds), A Musical Offering: Essays in Honour of Gerard Gillen (2018) (Journal of the Society for Musicology in Ireland, 2019)
A review of Kerry Houston and Harry White (eds), A Musical Offering: Essays in Honour of Gerard Gillen (Dublin: Four Courts Press, 2018). ISBN 978-1-84682-658-0